2016
DOI: 10.1128/jb.00120-16
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Erp Protein of Mycobacterium tuberculosis with Rv2212 Enhances Intracellular Survival of Mycobacterium smegmatis

Abstract: The Mycobacterium tuberculosis exported repetitive protein (RvErp) is a crucial virulence-associated factor as determined by its role in the survival and multiplication of mycobacteria in cultured macrophages and in vivo. Although attempts have been made to understand the function of Erp protein, its exact role in Mycobacterium pathogenesis is still elusive. One way to determine this is by searching for novel interactions of RvErp. Using a yeast two-hybrid assay, an adenylyl cyclase (AC), Rv2212, was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…This interaction between Rv2212 and Erp was initially discovered by using a yeast two-hybrid assay baited with cytoplasmic Mtb Erp lacking a signal sequence (Mtb-ss Erp). Co-precipitation of full-length Erp from Mtb lysates using anti-Rv2212 antibodies confirmed the interaction and showed that it requires the AC domain of Rv2212 (Ganaie et al 2016).…”
Section: Multiple Host-associated Signals Activate Mtb Acsmentioning
confidence: 76%
See 3 more Smart Citations
“…This interaction between Rv2212 and Erp was initially discovered by using a yeast two-hybrid assay baited with cytoplasmic Mtb Erp lacking a signal sequence (Mtb-ss Erp). Co-precipitation of full-length Erp from Mtb lysates using anti-Rv2212 antibodies confirmed the interaction and showed that it requires the AC domain of Rv2212 (Ganaie et al 2016).…”
Section: Multiple Host-associated Signals Activate Mtb Acsmentioning
confidence: 76%
“…A similar molecular switch is predicted to occur in other bacterial ACs, including the mycobacterial AC Rv2212, although regulation of Rv2212 activity is more complex than that of AC Rv1264 (Abdel Motaal et al 2006;Ganaie et al 2016). AC Rv2212 is activated by pH and fatty acids (Abdel Motaal et al 2006), as well as by interaction with the mycobacterial virulence factor exported repetitive protein (Rv3810 or Erp) (Ganaie et al 2016). This interaction between Rv2212 and Erp was initially discovered by using a yeast two-hybrid assay baited with cytoplasmic Mtb Erp lacking a signal sequence (Mtb-ss Erp).…”
Section: Multiple Host-associated Signals Activate Mtb Acsmentioning
confidence: 77%
See 2 more Smart Citations
“…Remarkably, this strain displayed a substantial growth acceleration compared to the control strain within mouse macrophages, i.e., when stressful conditions for intracellular parasite are evident (Pedroza-Roldán et al, 2015 ). Similarly, the overexpression of Rv2212 in M. smegmatis resulted in an enhanced survival of bacteria within macrophages (Ganaie et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%